OCCURRENCE OF A CHLOROTIC SPOTTING DISEASE ON SOME VISCA SWEET POTATO HYBRIDS - Gapasin, Ruben M.; Suico, Ma. Leticia (Annals of Tropical Research, 1984)
A chlorotic spotting disease of sweet potato was observed during inspections conducted in September 1984 on the sweet potato varieties and hybrids grown in the experimental field of the Visayas State College of Agriculture (VISCA), Baybay, Leyte, Philippines. The disease is believed to be caused by a virus. It was found to occur on variety VSP-2 and the hybrids V7-27, V5-88, V3-44 and V3-180.